The effect of teaching history subjects in social studies course with digital games on student academic success and creative thinking - Fatih Pala (Innoeduca)
The purpose of this research is to investigate the impact of digital games on students' academic achievement and creative thinking in teaching historical subjects in social studies classes. The data for the research were collected using a mixed-methods model. The study group consists of 7th-grade students from two separate classes studying in a school affiliated with the Ministry of National Education within the boundaries of Erzurum province during the 2022-2023 academic year. Class A represents the experimental group, while Class B represents the control group. A total of 62 students participated in the research, with 31 in the experimental group and 31 in the control group. The quantitative data of the research were collected through Torrance Creative Thinking Test Verbal A-B Forms, an academic achievement test developed by the researcher, and a teacher observation form. The qualitative data were gathered using a semi-structured interview form developed by the researcher. The quantitative data analysis of the research was conducted using the SPSS 21.0 package program. A normality test was performed to determine whether the data followed a normal distribution. Parametric tests such as "Paired Samples t-test, Independent Samples t-test, and ANOVA" were used for the analysis of data showing normal distribution, whereas non-parametric tests like "Mann Whitney U Test and Wilcoxon Signed-Rank Test" were utilized for data that did not exhibit normal distribution. The qualitative data of the research were collected through the "Interview Form" and analyzed using content analysis with the MAQODA 20 analysis program. As a result of the research, it was concluded that digital games increased students' academic achievement and encouraged creative thinking. Additionally, according to student opinions, digital games influenced digital principles, creative thinking activities, and types of games. Students faced challenges in creating video games, particularly with video and writing applications during the process of digital game creation. In the research, considering that some students are more engaged in the fun and creative activities of lessons conducted through digital games, efforts should be directed towards enhancing student creativity and fostering a greater focus on learning. Given the recent development of digital games in various aspects of life, there is a need for further research in the field of digital game applications for educational purposes.